Implementation of Anti-Corruption Education in Piaud Study Program in IAIN Takengon - Marlina Marlina; Evanirosa Evanirosa; Wajnah Wajnah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study is to examine the implementation of anti-corruption education in the PIAUD IAIN Takengon study program, to find out the impact of the application of the anti-corruption education model, and to see whether the anti-corruption education program model is more students' mastery of it. This research is a qualitative descriptive study. The research subjects were 75 students from the VII semester IAIN Takengon PIAUD. The data collection techniques used questionnaires and in-depth interviews and were analyzed by data reduction, data presentation and data verification. The results showed that the implementation of the anti-corruption education curriculum model was not 100% pure applying the course model itself, but integrated learning indirectly as a habit to provide advice. The implementation of the anti-corruption education model is sufficient to provide an understanding for students to study corruption. The curriculum model with the subject itself is still the best model for providing knowledge to students on anti-corruption material, but with the addition of learning outside the classroom curriculum.